COMBINING THE ENGLISH AND THE AI SKILL AS THE PANACEA FOR BEING EMPLOYABLE: THE CASE OF A STATE VOCATIONAL HIGH SCHOOL - Aam Alamsyah; Mutaat Mutaat; Theresia Mundi Astuti; Edy Supriyanto; Mahyati Mahyati; Tubagus Udong Rapiudin; Devian Try Gustary; Anggit Laesa Oktaviani (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2025)
Every year, Technocrat Foreign Language School (hereinafter referred to as STBA Technorat Tangerang) conducts annual community service for the surrounding communities. In 2025, STBA Technocrat conducted the training at the same venue, namely The 4th Vocational High School in Tangerang. The community service was conducted in line with Law Number 12 of 2012 concerning Higher Education—the training aimed to provide students with higher-quality English instruction, thereby improving their employability skills. The training incorporated AI as one of the learning sources. The present study aimed to both report the results of the English training and to identify students’ perceptions of their English training, their preferred future employment, and the incorporation of AI into their learning materials. The study was conducted after the training was completed. Forty students from different departments attended the training. The students who joined the training were active members of the English club. The study used a mixed-methods design to capture more data on students’ perceptions of the other aforementioned important matters. The findings indicated that most students expressed positive perceptions of the training provided by the English college. They also indicated different preferences for their future jobs. Specifically, some jobs were identified as popular, such as office/factory work, hospitality, banking, and retail. Regarding incorporating AI, they perceived that it helped them improve their speaking skills. They also thought that, despite being a necessity, AI could not create a natural atmosphere for communication. In fact, both teachers and students are responsible for fostering such an occasion in which the students can speak more naturally and enjoyably.